Expression of a rice soluble starch synthase gene in transgenic wheat improves the grain yield under heat stress conditions - Tian, Bin; Talukder, Shyamal K.; Fu, Jianming; Fritz, Allan K.; Trick, Harold N. (In vitro cellular & developmental biology. Plant, 2018)
Wheat (Triticum aestivum L.) is a temperate cereal with an optimum temperature range of 15–22°C during the grain filling stage. Heat stress is one of the major environmental constraints for wheat production worldwide. Temperatures above 25°C during the grain filling stage significantly reduced wheat yield and quality. This reduction was reported due to the inactivation of the soluble starch synthase, a key heat-labile enzyme in starch transformation of wheat endosperm. To improve wheat productivity under heat stress, the rice soluble starch synthase I, under the control of either a constitutive promoter or an endosperm-specific promoter, was expressed in wheat and the transgenic lines were monitored for expression and the effects on yield-related traits. The results showed that the transgenic wheat events expressed rice soluble starch synthase I at a high level after four generations, and transgenic plants produced grains of greater weight during heat stress. Under heat stress conditions, the thousand kernel weight increased 21–34% in T2 and T3 transgenic plants compared to the non-transgenic control plants. In addition, the photosynthetic duration of transgenic wheat was longer than in non-transgenic controls. This study demonstrated that the engineering of a heat tolerant soluble starch synthase gene can be a potential strategy to improve wheat yield under heat stress conditions.